Prediction of Chinese Reading Fluency by Verbal and Non-verbal Visual Attention Span Measures - Chan, Kevin Shing-Chi; Yeung, Pui-Sze (Frontiers in Psychology, 2020)
The present study explored 1) the relationship between verbal and nonverbal visual attention span measures, and 2) the relationship between visual attention span and word reading fluency in traditional Chinese among 100 higher education students in Hong Kong. Participants’ visual attention span was assessed by verbal measures (i.e., global report task, partial report task) and nonverbal measures (i.e., visual 1-back task with Chinese characters and visual 1-back task with nonverbal stimuli). Results of confirmatory factor analysis indicated that the single latent factor model, composed of global report task, partial report task, visual 1-back task with Chinese characters and visual 1-back task with nonverbal stimuli, was a good fit to the data. Regression analysis showed that verbal measures for visual attention span (i.e., global report task and partial report task) significantly predicted word reading fluency in traditional Chinese. Structural equation modelling showed a significant predictive relationship between the single latent factor composed of verbal and nonverbal measures for visual attention span, and word reading fluency in traditional Chinese. The results showed that visual attention span applied to explain reading fluency in traditional Chinese.